Penerimaan Masyarakat Kepada Penyandang Disabilitas : (Studi Desa Inklusi Peduli dengan Kelompok Rentan di Kalurahan Sidorejo, Kapanewon Lendah, Kabupaten Kulon Progo) - Sri Murwaningsih; Ratna Sesotya Wedjajati (SOSIO PROGRESIF | Media Pemikiran Studi Pembangunan Sosial, 2021)
Persons with disabilities are included in the marginalized group because of their lack of ability to interact and have difficulty joining community groups. This research looks at the impact of the emergence of "Inclusion Village" as part of the Rindi (Rintisan Desa Inklusi) program of the Kulon Progo Regency Government. This study uses a descriptive method with a qualitative approach. The object of this research is the situation of the Inclusion Village in community acceptance of people with disabilities. Information was collected from 15 disabled people, 3 families with disabilities and 3 communities. One of the factors that causes people with disabilities in Sidorejo Village to be able to join social groups in the community is support from their families. The community does not object to the presence of people with disabilities in social groups because people with disabilities are able to adapt quickly, and people make people with disabilities as motivation to increase their racial gratitude and respect for time. Villages provide opportunities, facilities and involve people with disabilities in community activities.